Penerapan Pendekatan Saintifik Pada Pembelajaran Seni Tari Oleh Guru Kelas VII.10 Di SMP Negeri 2 Kota Solok - Meisa Adila; Indrayuda Indrayuda; Darmawati Darmawati (SENDRATASIK UNP, 2019)
This article aims to find out and describe the application of the Scientific Approach to the study of Dance Class VII. 10 in SMP Negeri 2 at Solok. This type of research is qualitative research using descriptive method. The instrument of this study is the researchers themselves. Types of data using primary data secondary dandata. Engineering data collection done by the study of librarianship, observation and interview. After the data is collected, the data analyzed by a conceptual framework based on. The results showed that the application of scientific approaches in the study of art and culture (dance) are going well and the students gave positive response during learning activities. At the first meeting there were still many students who are making a fuss, not excited in the move, and not confident in doing the motion. At the second meeting has already increased the student who submits an opinion. At the third meeting of the visible increase in the activity of students i.e. students who dared to ask your opinions and ask questions. Student activity on the fourth and fifth meetings already looks very good. That's where almost all serious and eager students in learning theory as well as practice of dance. Then follows the application of scientific approaches in the study of art and culture (dance) is very effective in improving student learning activities.